2014
DOI: 10.1002/uog.13323
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in gynecological disease (10): clinical and ultrasound characteristics of decidualized endometriomas surgically removed during pregnancy

Abstract: Objectives To describe the clinical history and ultrasound findings in women with decidualized endometriomas surgically removed during pregnancy. Methods In this retrospective study, women with a his

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 25 publications
2
40
0
2
Order By: Relevance
“…Ultrasound examiners should always take into account the phenomenon of decidualisation, which is a major contributory factor to incorrect diagnosis in pregnant women [21]. Most decidualised endometriomas (82%) were described as manifesting vascularised rounded papillary projections with a smooth contour in an ovarian cyst with one or more cyst locules and ground glass, or low level echogenicity of the cyst fluid [22]. …”
Section: Endometriomas and Malignancymentioning
confidence: 99%
“…Ultrasound examiners should always take into account the phenomenon of decidualisation, which is a major contributory factor to incorrect diagnosis in pregnant women [21]. Most decidualised endometriomas (82%) were described as manifesting vascularised rounded papillary projections with a smooth contour in an ovarian cyst with one or more cyst locules and ground glass, or low level echogenicity of the cyst fluid [22]. …”
Section: Endometriomas and Malignancymentioning
confidence: 99%
“…In the present case, both ovaries were normal and a retro‐uterine fast‐growing solid mass was described. Although ultrasound pattern recognition of decidualized endometrioma was recently described by Mascilini et al , there are no cases in the literature of decidualized atypical endometriotic localization, as in the present case …”
Section: Discussionmentioning
confidence: 57%
“…In our study, 8 of 21 masses had at least 1 septation, and 1 mass had developed a septation on follow‐up examination, suggesting that this characteristic is not a useful distinguishing feature in our population. Mascilini et al 9 evaluated 18 cases of decidualized endometriomas gathered from 7 centers (including patient 3 in this study). They found that 15 of the 18 decidualized endometriomas contained rounded papillary projections with a smooth contour and suggested that these rounded papillations were different from those associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…These inclusion criteria generated a study population of 17 patients with 22 adnexal masses. One case (patient 3) was also included in a previous multicenter study by Mascilini et al 9 but was not deleted from our cohort due to the consecutive and inclusive design of our own study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation